PS 11-52 HEALTHY OBESITY SUBJECTS WITH HYPERTENSION SHOWS FAVORABLE CIRCADIAN RHYTHM IN HEART RATE AND BLOOD PRESSURE COMPARED WITH PATHOLOGIC OBESITY: KOREAN REGISTRY OF TARGET ORGAN DAMAGES IN HYPERTENSION (KorHR). (September 2016) - Cho, Eun Joo; Yoo, Byung Su; Shin, Mi Seung; Sung, Ki Chul; Kim, Eung Ju; Han, Seong Woo; Ryu, Kyu Hyung
Abstract : Objective: Metabolically healthy obesity is more advantageous in cardiovascular outcome than pathologic obesity. This study was to evaluate blood pressure (BP) and heart rate (HR) using 24-hour ambulatory BP monitoring and to compare among various type of obesity and non-obesity hypertensives. Design and Method: Korean Registry of Target Organ Damages in Hypetension (KorHR), established since March 2013 was nation-wide prospective observation study including 16 tertiary care hospitals. Total 1654 hypertensive subjects aged more than 30 years old without history of obvious cardiovascular disease were divided into 4 groups according to body mass index (BMI) and waist circumference (WC). (table) Office BP and 24-hour ambulatory BP with HR were measured with other laboratory data. Results: Total 1096 subject's [mean age = 51.4 ± 11.9 years, including 699 (63.8%) male and 524 (47.8%) naïve hypertensives] BMI and WC data were available. There were no significant differences in lipid profile, hs-CRP and HbA1C levels among various obesity groups (group 1, 2 and 3). However, the 24-hour mean SBP was significantly lower in group 3 compared with other groups. (138.7 ± 15.0 vs. 137.8 ± 12.7 vs. 133.1 ± 17.6* vs. 136.5 ± 14.0, *p = 0.016 vs. other groups) Early morning HR was significantly lower in group 3 (71.1 ± 11.4 vs. 66.2 ± 12.2* vs. 66.2 ± 11.8* vs. 69.6 ± 11.9 bpm, *p = 0.026 vs. group 1) and dipper pattern showed strong tendency of more prevalent in group 3 and 4 with intermediate significance. The results were consistent in both naïve population and patients with anti-hypertensive medications. Conclusions: Healthy obesity hypertensives showed more favorable circadian rhythm in BP and HR than pathologic obesity regardless of metabolic profiles and history of anti-hypertensive medication. This would be a mechanism of advantageous cardiovascular outcome in healthy obesity hypertensives.